Green Kampong Management Using a Participatory Community Approach - Nafiah Solikhah; Titin Fatimah; Mega Kusumawati; Alifia Lufthansa (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The urban kampong ‘kampung kota’ is an essential part of the formation of city structures. One existing urban kampong in Jakarta is kampung Tanjung Gedong, located at RT 05/RW 08, Tomang Sub-district, Grogol Petamburan District in West Jakarta. Its location, which is 500 meters from Untar Campus 1, was one consideration for selecting kampung Tanjung Gedong as a partner. The team has also carried out community service activities (PKM) in this location, and it is expected that the program implemented would be sustainable. In the context of urban life, kampung Tanjung Gedong has physical, spatial, and environmental problems, mainly due to the high level of building density. The purpose of these activities was to provide a solution for urban village management using a participatory community approach. The proposed solution is penataan Kampung Hijau ‘Green Kampong Management’ by involving community members’ active participation from the beginning of the planning to the management through the placemaking method, which involves three approaches: green planning and design, green open space, and green community. This proposed green kampong concept is expected to overcome the problems encountered by the partner in achieving a healthy and comfortable environment for residents. The concept of green kampong is a promising solution in solving the physical environmental and spatial problems of kampung kota Tanjung Gedong. The program has improved the quality of the environment and increased the community's social quality in a form of a healthier lifestyle.